POTATO IN INDIA: EMERGING TRENDS AND CHALLENGES IN THE NEW MILLENNIUM - Pandey, S. K.; Sarkar, D (Potato Journal, 2013)
Potato (Solanum tuberosum L.), a New World tuber crop of the antiquity, has historically contributed to securing the food and nutrition, and avoiding the poverty and hunger. In the emerging global economic order in which agricultural crop production is witnessing a rapid transition to agricultural commodity production, potato is appearing as an important crop, poised to sustain and diversify food production in this new millennium. In developing countries, particularly in India, it has substantially contributed to sustaining the food production over the past five decades in the last millennium. However, this new millennium, which is characterized by increasing globalization, growing concern on environment, added importance to food safety and rising importance of intellectual property rights (IPR), sets enormous challenges for potatoes not only to connect the millions of poor small/ marginal farmers to the international market, but also to provide safety nets for poor households struggling to avoid poverty and hunger. Technological progress in emerging processing sectors, development and diffusion of quality-enhancing as well as yield-increasing technologies, institutional innovations and policy changes geared towards sustaining the resource base while increasing the supply and demand and good governance for facilitating the techno-economic feasibility for the promotion of international potato trade in the global market are some of the key issues emerging at the very beginning of this millennium. Against this millennium backdrop and growing environmental concern, there is an added challenge to increase the productivity and profitability of the potatoes with sustainable management of the environment. Sustainable potato production calls for an integrated resource management scheme utilizing optimum utilization of land, water, nutrient and energy. The article analyzes the emerging trends in potato production in India with reference to other developing countries, re-examines the challenges encountered in the last millennium, and attempts to prioritize the challenges likely to be encountered in this millennium.